Contribuição ao conhecimento químico de espécies de Hyptis com ocorrência no semiárido paraibano: Hyptis macrostrachys Benth. e Hyptis umbrosa Salzm. Ex Benth. - Costa, Vicente Carlos de Oliveira (2013)
Lamiaceae family has 295 genera and about 7,775 species with cosmopolitan distribution. It is estimated that 22 genera and 402 species occur in Brazil. This study describes the phytochemical study of two species of the genus Hyptis found in semiarid Paraiba, Hyptis macrostachys Benth. and Hyptis umbrosa Salzm. ex Benth. Leaves and stems of the species studied were subjected to extraction and subsequently processes of filtration and chromatography of their extracts. Posteriorly, chemical structures of the isolated compounds were identified and/or determined by spectroscopic methods. The crude ethanol extract (CEE) of Hyptis macrostachys obtained phases hexane, and dichlorometane and ethyl acetate. In study of dichlorometanic phase from H. macrostachys were isolated five substances by conventional chromatographic methods: two diterpenes, beier-15-en-17-ol (erytroxilol B) encoded as Hm-1, isolated as before and ent-labda (8)-17.14-dien,9,13-epoxy-12α-hydroxy-19-oic acid (Hm-3) unpublished literature (hyptenol); two triterpenes, 3-β-acetoxy-olean-12-en-28-oic (acetate oleanolic acid) and 3β-hydroxy-lup-20 (29)-on-28-oic acid (betulinic acid), have previously been isolated from species of Hyptis (Hm-2 and Hm-4, respectivety), plus a pyrone 6R-[(5'S, 6'S-diacetoxy)-1'Z, 3'E-heptenyl]-5,6-dihydro-2H-pyran-2-one (Hm-5), unpublished literature (hyptenolide). From ethyl acetate phase two triterpens have been isolated, a mixture of ursolic and oleanolic acids (Hm-6) and 2α,3β,19α-trihydroxy-urs-12-en-28-oic acid (tormentic acid), encoded as Hm-7. The CCE from Hyptis umbrosa was subjected to medium pressure chromatography. The fractions were monitored by TLC and assembled according to their chromatographic profiles. In CEE of Hyptis umbrosa, two diterpens were isolated, pomifrim D (Hu-1) first reported in this species, but its NMR data were completely reassignment and salviol (Hu-2), previously isolated from other species of Lamiaceae family. How many species of Lamiaceae are known to have significant amount of essential oils, it was decided to analyze the fresh leaves of Hyptis macrostachys and Hyptis umbrosa was extracted by hydrodistillation in clevenger apparatus and characterized by GC-MS. The chemical constitution of the essential oils of Hyptis macrostachys and Hyptis umbrosa was 98.37 and 92.9%, respectively, of monoterpenes and sesquiterpenes. Being 1,8-cineole (36.3%) the major constituent for Hyptis macrostachys and fenchona (24.8%) for Hyptis umbrosa, consistent with the chemical composition of essential oils of other species of Lamiaceae. These results contributed to the phytochemical study of the species of the semiarid of Paraíba, H. macrostachys and H. umbrosa with the structural identification of nine substances, two of the unpublished (hyptenol and hyptenolide).